EFFECT OF 5 WT.% WPCB POWDER AS REDUCTANT ON INDONESIAN NICKELIFEROUS ORE PROCESSING - Reza Miftahul Ulum; Dimas Ananda Radhitya; Alfian Ferdiansyah Madsuha; Faizinal Abidin (Jurnal Sains Materi Indonesia, 2020)
EFFECT OF 5 WT.% WPCB POWDER AS REDUCTANT ON INDONESIAN LIMONITICNICKEL ORE PROCESSING. Waste printed circuit boards (WPCB) are among the most valuable parts of electronic waste with one of the fastest-growing waste streams in the world. The purpose of this study is to investigate the possibility of WPCB powder as an alternative reducing agent for the carbothermic process in nickel lateritic ore processing. WPCB waste was mixed with nickel ore at 1100ÚC in inert atmosphere. In addition, a conventional reductant of coal is also utilized for comparison. Both reductant are varied in concentration of 5 wt% and 15 wt%. Based on thermogravimetric analysis (TGA) and differential thermogravimetric analysis (DTA) investigation, it is observed that there exists a difference between WPCB powder, nickeliferous ore powder, and the mixture in their decomposed levels. The decomposed gasses of WPCB produced by thermal degradation in the TGA instrument are mainly composed of reduction gas, which plays a critical role in reducing the nickeliferous ore. This study shows that WPCB powder performs comparably to sub-bituminous coal in the pyrometallurgical processing of nickel ore, which is proved by X-Ray Diffraction (XRD) test results that the carbothermic products consists of FeNi, magnetite, wustite and fayalite. It can be concluded than WPCB powder has potential to be utilize as an alternative reductant.